Unlocking Modulation Rule of Heterointerface Engineering Induced D‐Band Center on Polysulfides Conversion in Lithium–Sulfur Batteries - Wenbin Li; Ni Wang; Jingjie Pei; Dongyan Li; Guiqiang Cao; Ruixian Duan; Jingjing Wang; Xifei Li (Advanced Science)
Abstract MOF‐derived heterostructures have been widely utilized as S hosts to address the three issues faced by the sulfur (S) cathode in lithium–sulfur batteries. Precisely pinpointing the active center in the heterostructure and unlocking the modulation rule of heterostructure on polysulfides (LiPSs) conversion are particularly important. Herein, the two homologous hetero‐hosts of ZIF‐67‐derived CoSe2@CoSe0.25S1.75/NC and CoSe2@CoS2/NC nanoparticles anchored in the nitrogen‐doped carbon (NC) matrix are successfully constructed, and confirm that Co at the heterointerface is the primary active center, rather than Co within the individual phases. It is revealed that the ɛd (d‐band center) of Co in the heterostructure can be a significant descriptor for the adsorption ability and conversion ability to LiPSs, and the discharge‐specific capacities, which describe a volcano curve as a function of εd. It is also found that the best Li+ storage property appears at CoSe2@CoSe0.25S1.75 heterointerface among the five structures (CoSe2@CoSe0.25S1.75, CoSe2@CoS2, CoSe0.25S1.75, CoSe2, CoS2). The capacity is up to 600 mAh g−1 with a large retention rate of 73.3% at 0.2 C after 100 cycles, and the capacity decay rate is only 0.083% per cycle at 1 C during 300 long‐cycling process.